Coherentismo versus confiabilismo - Pinto, Sílvio (Revista de Filosofía, 2005)
Recently, a number of epistemologists has adopted some sort of reliabilism. According to them, we must reject classical types of internalism such as foundationalism and coherentism. Here, I will resist this tendency of contemporary epistemology by defending a version of coherentism. My strategy will consist in demonstrating that the latter offers a more satisfactory answer to the problem of how the epistemic justification of our best belief systems relates to their supposed truth.
Keywords: Coherentism; Reliabilism; Justification; Truth; Normativity